Raised ?2-Microglobulin as a Surrogate Marker in Non-Secretory Multiple Myeloma - Agrawal, Bimal K; Sehgal, Anshul; Deswal, Vikas; Singh, Prem; Agrawal, Usha (Bangladesh Journal of Medical Science, 2017)
Multiple myeloma is a neoplasm of plasma cells in the bone marrow. It is characterised by lytic lesions in the bones, marrow plasmacytosis and presence of M protein in serum and/or urine. Serum ?2 microglobulin is also raised and can be used for classification and prognostication of the disease. In the absence of M protein, the disease is known as non-secretory myeloma. It is proposed that raised ?2 microglobulin can be used for diagnosis and therapeutic guidance in the absence of M protein. A rare case of nonsecretory myeloma with neurocognitive impairment along with review of literature is being presented. The patient had multiple lytic lesions in bones with marked increase in plasma cells in bone marrow. M protein was not detectable in serum or urine but serum ?2 microglobulin was much elevated. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.142-145